L-glutamine and L-alanine supplementation increase glutamine-glutathione axis and muscle HSP-27 in rats trained using a progressive high-intensity resistance exercise - Leite, J.; Raizel, R.; Hypólito, T.; Dos Santos Rosa, T.; Cruzat, Vinicius; Tirapegui, J. (N R C Research Press, 2016)
In this study we investigated the chronic effects of oral L-glutamine and L-alanine supplementation, either in their free or dipeptide form, on glutamine-glutathione (GLN-GSH) axis and cytoprotection mediated by HSP-27 in rats submitted to resistance exercise (RE). Forty Wistar rats were distributed into 5 groups: sedentary; trained (CTRL); and trained supplemented with L-alanyl-L-glutamine, L-glutamine and L-alanine in their free form (GLN+ALA), or free L-alanine (ALA). All trained animals were submitted to a 6-week ladder-climbing protocol. Supplementations were offered in a 4% drinking water solution for 21 days prior to euthanasia. Plasma glutamine, creatine kinase (CK), myoglobin (MYO), and erythrocyte concentration of reduced GSH and glutathione disulfide (GSSG) were measured. In tibialis anterior skeletal muscle, GLN-GSH axis, thiobarbituric acid reactive substances (TBARS), and the expression of heat shock factor 1 (HSF-1), 27-kDa heat shock protein (HSP-27), and glutamine synthetase were determined. In CRTL animals, high-intensity RE reduced muscle glutamine levels and increased GSSG/GSH rate and TBARS, as well as augmented plasma CK and MYO levels. Conversely, L-glutamine-supplemented animals showed an increase in plasma and muscle levels of glutamine, with a reduction in GSSG/GSH rate, TBARS, and CK. Free L-alanine administration increased plasma glutamine concentration and lowered muscle TBARS. HSF-1 and HSP-27 were high in all supplemented groups when compared with CTRL (p < 0.05). The results presented herein demonstrate that L-glutamine supplemented with L-alanine, in both a free or dipeptide form, improve the GLN-GSH axis and promote cytoprotective effects in rats submitted to high-intensity RE training.